2018
DOI: 10.1111/cote.12370
|View full text |Cite
|
Sign up to set email alerts
|

The application of biosurfactants for scouring wool

Abstract: The first investigation of the use of biosurfactants for the scouring of raw wool is reported. A saponin, and a recently developed surface active oat extract, were evaluated at the laboratory scale using a first-to-bereported benchtop scouring system with simulated flowback. The levels of contaminants remaining on the wool after bioscouring, along with the wool colour, were compared with those of wool that had been laboratory-scoured with a surfactant used in the commercial scouring of raw wool, namely a synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…A biosurfactant producing Cobetia marina is patented as an additive of paint formulation for submersible surfaces ( Dinamarca-Tapia et al, 2012 ). Rhamnolipid ( Raza et al, 2014 ) and saponin ( Leighs et al, 2018 ) are reported for scouring cotton fibers and wools, respectively. The biosurfactant-producing Meyerozyma guilliermondii and Acidithiobacillus spp.…”
Section: Applications Of Biosurfactantsmentioning
confidence: 99%
“…A biosurfactant producing Cobetia marina is patented as an additive of paint formulation for submersible surfaces ( Dinamarca-Tapia et al, 2012 ). Rhamnolipid ( Raza et al, 2014 ) and saponin ( Leighs et al, 2018 ) are reported for scouring cotton fibers and wools, respectively. The biosurfactant-producing Meyerozyma guilliermondii and Acidithiobacillus spp.…”
Section: Applications Of Biosurfactantsmentioning
confidence: 99%
“…Due to its outstanding adhesive characteristics, the surfactant of amino acid is an ideal softening agent and lubricant in textiles [74,75]. Biosurfactants are accepted in the replacement of petroleumbased surfactants due to their sustainability, biodegradability, less effluent load, being economically viable, and cheaper starting material (the leather waste in this case) [76]. As a result, an amino acid-based surfactant can be the potential replacement for petroleum-based surfactants for textile applications.…”
Section: Biosurfactant Applications In Textilementioning
confidence: 99%
“…The use of eco-friendly biosurfactants is an alternate approach for lowering environmental impact. Studies on the application of biosurfactants in scouring are limited, mainly consisting of the plant-based biosurfactant saponin from Quillaja Saponara, and oat extract [38,39].…”
Section: Introductionmentioning
confidence: 99%